DESIGN OF A MACHINE FOR CHOPPING COCONUT FIBER INTO COCONUT POWDER (COCOPEAT) WITH A CAPACITY OF 70 KG/HOUR - Muhammad; Nani Sri Rezeki; Samuel Haris Purba (Journal of Golden Generation Engineering, 2025)
The coconut fiber shredding machine is a tool in the production sector that plays an important role in the process of chopping coconut fiber into coconut fiber, so that it can be used as several useful products. The objectives to be achieved in designing this coconut fiber shredding machine are: Knowing the manufacture of a coconut fiber shredding machine with a capacity of 70 kg / hour. Can design and calculate the components of a cocopeat machine that can chop coconut fiber quickly and with greater capacity. Knowing the power of the driving motor used. For the development of knowledge and applying it in the form of design and research. The design of a coconut fiber shredding machine with a capacity of 70 kg/hour, the following conclusions were obtained: Shaft diameter 25 mm, Pin size l = 7 mm, t = mm, p = 20 mm, Bearing number 6005, Motor pulley 50.8 mm (2 inches), Shredder knife shaft pulley 254 mm (10 inches), Belt length 1473 mm (58 inches) type A, Gasoline motor type with 5.5 Hp power, 3600 rpm rotation.